Assessment of waste separation at source by residential households as a tool for sustainable waste practices: a case study of the City of Johannesburg - Kadyamadare, Grace Alice Rudo (My University, 2017)
In Johannesburg, as in many cities of developing countries, municipal solid waste management poses a key challenge to local city governments. The amount of municipal solid waste generated has been noted to be growing in tandem with increasing city populations. This Masters Research Report focuses on the factors shaping participation in the separation at source (S@S) programme run by Johannesburg’s Pikitup waste management utility, with a particular focus on the role of residents’ conceptualization of waste. The research employed a qualitative comparative case study of two suburbs that were part of Pikitup’ first pilot S@S programme, which was conducted by the Waterval depot: the low income area of Newlands, and the high income area of Franklin Roosevelt Park. Twenty semi-structured interviews and one focus group interview were conducted in each of the suburbs, as well as three semistructured interviews with key informants. Findings were analyzed using thematic content analysis. The results indicate several differences between the two suburbs – including participation rates, conceptualization of waste and other factors shaping wasting practices. The research showed that conceptualization of waste is an important factor, but not the only one and affirmed other studies showing the importance of time, convenience and positive attitude towards recycling. The research found that in addition to their conceptualization of waste, the ways in which residents conceptualized recyclables affected their participation rates, and that their separation practices were aligned to their conceptualizations. In addition, the research found that residents’ conceptualization of recyclables and the recycling system played an important role in their decision to participate in Pikitup’ S@S programme. In Newlands, whilst some separated but due to their low incomes they sold it for themselves versus giving it to Pikitup, and others would not separate as they felt Pikitup should pay them or it was time consuming for them. In both suburbs those that understood the role of waste pickers chose to separate their waste for the waste pickers versus Pikitup. In conclusion, when we understand that residents participating in separating materials for different pathways, and waste pickers play an important role in separating at source when residents fail to do so then a better understanding of how much waste is being separated and diverted from landfills is obtained in addition to what motivates participation in separation. Keywords: municipal solid waste (MSW), resident households, conceptualization of waste, separation at source, wasting practices, waste picker
A research report presented in partial fulfillment of the requirements for the degree of Master of Science in Environmental Science at the University of the Witwatersrand. Johannesburg, August 2017.
Keywords: Refuse and refuse disposal--South Africa--Johannesburg; Recycling (Waste, etc.)--South Africa--Johannesburg